Las adaptaciones curriculares y su incidencia en la inclusión educativa de las y los estudiantes con nee, en el Colegio Fiscal “Atahualpa”, de la Parroquia de Amaguaña, Cantón Quito, Provincia de Pichincha, durante el año lectivo 2015 – 2016. - Carranza Moreno, Jorge Aníbal (2016)
The research has been of enormous importance and it has allowed teachers to understand that the regular educative system has a lack of knowledge about the Curricular Adaptations’ importance in the educative inclusion process of students with special educational needs associated or not with a disability, for this reason, this research has been done to help solve the educational problems of student diversity, generating a proposal to optimize the educational status, adaptation, school performance, promoting and strengthening into an integral development. Research to be located in the field of Social Sciences uses qualitative-quantitative approach that seeks to analyze a social and educative problem, especially human, in which is involved various actors, students, parents, and teachers. Field research was performed to parents, teachers and students of basic higher. In which, it was possible to obtain conclusions and recommendations to propose strategies and activities in order to help solving the socio-educational problems. Finally the proposal of a methodological manual development for the elaboration of curricular adaptations are made that it will serve as an advice source and support for the teachers educational work; strengthening the integral training of the student with special educational needs. It will let to improve their adaptation to the regular educational system and integrate them with responsibility to their integral professional training.